High throughput proteome and phosphorpoteome sample processing coupled to fast gradient DIA - Stoychev, Stoyan; Bekker-Jensen, Dorte; Martinez del Val, Ana; Steigerwald, Sophia; Batth, Tanveer; Gerber, Isak; Jordaan, Justin; Olsen, Jesper; Chien, Allis; Knudtson, Kevin; Martin, Roy (Journal of biomolecular techniques, 2020)
This work focusses on the application of high throughput workflows for proteome and phosphoproteome profiling followed by fast gradient liquid chromatography (LC) coupled to data-independent acquisition (DIA) mass spectrometry analysis. Automation of sample preparation increased throughput and reproducibility covering all steps from protein extract to mass spectrometry analysis allowing for parallel processing of up-to 96 samples in less than 6 hours (excluding digest time). We show the adaptation of the sample preparation methods including protein capture, clean-up, and on-bead digestion as well as phosphopeptide enrichment for use in a magnetic handling stations (Thermo Scientific King Fisher Flex) allowing for semi-automated sample processing. The methods are readily transferable to a range of liquid handling robots with magnetic handling stations (capabilities). Efficient protein isolation from wide range of tissues was achieved using 5% SDS followed by aggregation-based protein capture method (PAC) on MagReSyn® Amine magnetic microparticles allowing for efficient contaminant removal and on-bead digestion. For phosphoproteome profiling the PAC-generated peptides were further processed using MagReSyn® Ti-IMAC HP magnetic microparticles. All steps except for plate aliquoting and desalting were performed using a magnetic handling station that allowed for automated processing of up-to 96 samples in parallel. 500 ng peptides or enriched phosphopeptides were loaded directly on Evotips and further analysed using 21-minute gradients on Evosep LC coupled to Orbitrap Exploris equipped with FAIMS source allowing for up-to 60 samples per day to be analysed. Over 8,000 proteins and 22,000 unique phospho-peptides were quantified across the 12 tissues in a total mass spectrometry time of 28 hours.